2020
DOI: 10.1088/1757-899x/871/1/012078
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of the Effective Sintering Temperature on Electrical and Structural Properties of HgBa2Ca2Cu3O8+δ Compound

Abstract: : The HgBa2Ca2Cu3O8+δ specimens are manufactured via solid status interaction process at various temperature of sintering at ( 1073, 1123 and 1173 ) K. All the specimens in the immediately studied were submited to common constructional description by X - radiation deviation. The X - radiation deviation data combined from different samples agree with ( Hg - 1223 ) stages, then the investigations indicated that tetragonal construct for all specimens with an increasing in the dimension c to 15.87 A and reducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The volume fractional drop from 73 to 71 % when the amount of lead in the samples grew from x = 0.0 to 0.05, which is another factor contributing to the rise in critical temperatures brought on by the preference for the high phase 1223 over the other phases 1212 and 1201. 20,21) The ratio of parameters c/a was calculated and recorded in Table 1, where it is generally observed that this ratio increases with increasing lead concentration.…”
Section: Lead Contents (X)mentioning
confidence: 99%
“…The volume fractional drop from 73 to 71 % when the amount of lead in the samples grew from x = 0.0 to 0.05, which is another factor contributing to the rise in critical temperatures brought on by the preference for the high phase 1223 over the other phases 1212 and 1201. 20,21) The ratio of parameters c/a was calculated and recorded in Table 1, where it is generally observed that this ratio increases with increasing lead concentration.…”
Section: Lead Contents (X)mentioning
confidence: 99%